The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14419/ijans.v8i1.27149
|View full text |Cite
|
Sign up to set email alerts
|

Quality of cesarean section nursing care and its reflection up-on women's satisfaction with labor experience

Abstract:  Women satisfaction is a crucial predictor for maintaining and monitoring the quality of health care and can inform service development and delivery.Aim: To evaluate the quality of cesarean nursing care at hospital of Mansura University, the outcomes of it preserve ad-vanceandsupportqualityof care and womensatisfaction. By using a descriptive design the study conducted at obstetrics and gynecology department in Mansoura university hospital. On a total of 200women had undergoingelective cesarean section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…In Tambuyzer et al's study, a statistically significant relationship was determined between patient participation and satisfaction (40). As determined by Abdelati et al, women who underwent cesarean section were not satisfied with the psychological care, continuity of care, and participation in decision-making processes in the provision of care (28). All these suggest that there is a need for regulations aimed at encouraging patient participation in the provision of care and increasing patients' satisfaction with nursing.…”
Section: Satisfaction With Nursing Care Of Women Who Give Birth By Ce...mentioning
confidence: 93%
See 1 more Smart Citation
“…In Tambuyzer et al's study, a statistically significant relationship was determined between patient participation and satisfaction (40). As determined by Abdelati et al, women who underwent cesarean section were not satisfied with the psychological care, continuity of care, and participation in decision-making processes in the provision of care (28). All these suggest that there is a need for regulations aimed at encouraging patient participation in the provision of care and increasing patients' satisfaction with nursing.…”
Section: Satisfaction With Nursing Care Of Women Who Give Birth By Ce...mentioning
confidence: 93%
“…The study results of Ogut and Uyar Hazar support our findings (20). On the contrary, Abdelati et al found that women who underwent cesarean section were not satisfied with their decision-making processes in participating in their care (28).…”
Section: Satisfaction With Nursing Care Of Women Who Give Birth By Ce...mentioning
confidence: 98%